STUDENTS’ SATISFACTION ON E-LEARNING AND IMPACT ON STUDENTS’ ACADEMIC ACHIEVEMENT: A PILOT STUDY - Shahdan, Tengku Noorainun Tengku; Che Ani, Sharliana; Elias, Sofia; Farhah, Siti; Taha, Nuzha Mohamed (Institute of Advanced Engineering and Science, 2020)
There are significant challenges on students? satisfaction for academic achievement based on e-learning (online learning) environment. E-learning did approve beneficial for student?s learning. Most universities in Malaysia felt that student academic achievement occur problems and obstacles, where technology can help to overcome it. This study took place at a Private Higher Education Institution (PHEI) in Selangor. A mix-method was applied that involves survey, where the respondents were 128 undergraduate students and semi-structured interview with 4 undergraduate students from Faculty of Education and Humanities (FEH). This is a pilot study and the respondents were given the survey to validate the items. The result found that the reliability of the items was 0.89 for e-learning environment?s dimensions: e-teaching quality, lecturer?s support, and tutorial supports. This can be concluded that students? successes in their academic achievement and satisfied with online learning. However, this study also indicates that there are other elements that make students? satisfaction which will discuss further on the next paper.